Proses Pembentukan Identitas Islam Siswa Madrasah Ibtidaiyah dalam Konteks Pembelajaran: Studi Grounded Theory - Khairullah Khairullah (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
Islamic identity is a crucial component in the education provided by Madrasah Ibtidaiyah, serving as a foundation for the formation of character and religious values among students. However, understanding of how students' Islamic identity is formed within the context of learning at madrasah is still limited. This study aims to develop a theory on the process of Islamic identity formation among students using a grounded theory approach. This research employs grounded theory methodology to explore and understand the dynamics of Islamic identity formation among Madrasah Ibtidaiyah students. Data were collected through in-depth interviews with students, teachers, and parents, as well as classroom observations and curriculum document analysis. The data analysis process was conducted iteratively to identify main categories and emerging themes, and to build a comprehensive theory on the identity formation process. The study found that the process of Islamic identity formation among Madrasah Ibtidaiyah students is influenced by a complex interaction between internal and external factors. Internal factors include personal religious understanding and learning experiences, while external factors encompass the influence of the school environment, curriculum, and family support. The findings indicate that students' Islamic identity is shaped through integrated learning experiences, social interactions, and deep personal reflection. This research develops a theory that describes how Islamic identity among Madrasah Ibtidaiyah students is formed within the learning context. The findings provide important insights for curriculum development and teaching strategies aimed at supporting the formation of students' Islamic identity. The implications of this study also highlight the need for stronger support from families and the school environment to facilitate a positive identity formation process.